Fortifikasi Daging Ikan Selar Kuning (Selaroides leptolepis) terhadap Kualitas Fisikokimia Mi Kering - Jenri Parlinggoman Hutasoit; Risty Adekantari (Study Program of Food Technology, Faculty of Agricultural Technology, Udayana University, 2026)
The increasing consumption of convenience foods, along with changes in modern lifestyles, has driven the need to develop noodle products with improved nutritional quality and based on local raw materials. Fortification of noodles through the substitution of animal protein offers a promising approach to enhance nutritional value while improving the physical characteristics of the final product. This study aimed to evaluate the effect of yellowstripe scad (Selaroides leptolepis) meat substitution on the nutrition composition and physical properties of dried noodles. A completely randomized design was applied with five levels of fish meat substitution, namely 0, 10, 15, 20, and 25%. Proximate parameters analyzed included moisture, protein, fat, ash, carbohydrate, and total energy contents, while physical properties comprised water absorption capacity, volume expansion, and cooking loss. Data were analyzed using analysis of variance (ANOVA) followed by Tukey’s test at a significance level of α = 5%. The results indicated that fish meat substitution significantly affected all evaluated parameters. Increasing substitution levels enhanced protein, fat, mineral, and moisture contents, while reducing carbohydrate content due to the substitution effect. These compositional changes were accompanied by improvements in noodle physical properties, as indicated by increased water absorption and volume expansion and reduced cooking loss. Despite the reduction in carbohydrate content, total energy remained relatively high due to contributions from protein and fat. The formulation with 25% fish meat substitution exhibited the most favorable nutritional quality and physical characteristics. Overall, yellowstripe scad meat substitution effectively improved the nutritional quality and cooking performance of dried noodles, indicating its potential for the development of high-nutritional-value noodle products based on local resources.